Lower Defeat Thresholds for Minority Shareholders and Corporate Governance: Evidence from the Australian “Two-Strikes” Rule - Bugeja, Martin; da Silva Rosa, Raymond; Shan, Yaowen; Walter, Terry; Yermack, David (The Accounting Review, 2023)
ABSTRACT This study assesses the impact of minority shareholder empowerment via lower defeat thresholds in “say-on-pay” votes on CEO compensation and career prospects for directors. We exploit the adoption of the Australian “two-strikes” rule as a quasi-exogenous shock, which empowers shareholders to vote on board dismissal if a firm’s remuneration report receives 25 percent or more dissent votes for two consecutive years. Using a difference-in-differences methodology, we find that firms respond to a “strike” by curbing excessive CEO pay. Under the two-strikes regime, independent directors are held more accountable for poor oversight and experience significant reputational penalties in terms of turnover and the loss of outside directorships subsequent to receiving a strike. The results are mainly driven by firms receiving a nonmajority strike, indicating that the effectiveness of the two-strikes regime stems largely from the lower defeat threshold. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G34.